2023
DOI: 10.1097/mcg.0000000000001896
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anti-Saccharomyces Cerevisiae Antibodies (ASCA) in Patients With Irritable Bowel Syndrome (IBS). A Case-control Study

Abstract: Background: Irritable bowel syndrome (IBS) is a disorder of gut-brain interaction that affects patients’ quality. Recent research has shown variations in the mycobiome of individuals with IBS, particularly involving Saccharomyces cerevisiae, and its association with dysbiosis and visceral hypersensitivity. However, the role of Anti-Saccharomyces cerevisiae antibodies (ASCA) in IBS remains unclear, despite their significance as markers of disease severity in inflammatory bowel disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Colocalization results confirmed that anti-CdtB binds to ICC and myenteric ganglia, both in rat models and human subjects ( Pimentel et al, 2015a ), which may influence the functions of the enteric nervous system (ENS). A Mexican study monitored anti- Saccharomyces cerevisiae antibodies (ASCA) in IBS patients and observed that 16.5% of IBS patients were positive for ASCA IgG, however ASCA IgG could not serve as discriminatory biomarker for distinguishing IBS patients for now ( Thomas-Dupont et al, 2023 ).…”
Section: Autoantibodies Documented In Ibs Patientsmentioning
confidence: 99%
“…Colocalization results confirmed that anti-CdtB binds to ICC and myenteric ganglia, both in rat models and human subjects ( Pimentel et al, 2015a ), which may influence the functions of the enteric nervous system (ENS). A Mexican study monitored anti- Saccharomyces cerevisiae antibodies (ASCA) in IBS patients and observed that 16.5% of IBS patients were positive for ASCA IgG, however ASCA IgG could not serve as discriminatory biomarker for distinguishing IBS patients for now ( Thomas-Dupont et al, 2023 ).…”
Section: Autoantibodies Documented In Ibs Patientsmentioning
confidence: 99%